PENGARUH Trichoderma spp Pada DEKOMPOSISI AMPAS SAGU - Tatuhey, Dominggus Marcus Donald; Lawalata, Jacob J.; Merahabi, Paskalius Apriyanto; Masbaitubun, Herman; Linggi, Mery I.A. (STIPER Santo Thomas Aquinas Jayapura, 2025)
Sago dregs are waste from processing sago plants, which can pollute the environment if not utilized. One way of utilizing it is as compost and planting media by using the fungal decomposer Trichoderma. This study aims to determine the effect of Trichoderma on the time of sago pulp composting. The experiment was designed according to a group randomized design, consisting of one treatment factor and five replicates. The results showed that; (1) The addition of Trichoderma affects the decomposition of sago pulp, (2) Trichoderma can accelerate the decomposition time with one parameter, namely temperature. The decrease in decomposition temperature occurred in the third week period, (3) The percentage of material shrinkage and dry weight of sago bagasse material given Trichoderma was significantly different from the control. The highest percentage of shrinkage was in sago bagasse added with 6 grams of Trichoderma.